Explaining institutional dynamics within local partnerships: the case of ‘EQUAL II’ and ‘LEADER+’ in Crete - Grigoriadou, Despoina (2013)
This neo institutional study analyses the dynamic interaction between formal/informal rules and agents’ behaviour inside a political institution, examining these relationships through primary research on local partnerships in Greece.